Penerapan Prinsip Kehati-Hatian Dalam Valuasi Hak Kekayaan Intelektual Sebagai Jaminan Fidusia - Iskandar, Sulthon Setyagama (JATIJAJAR LAW REVIEW, 2025)
PENERAPAN PRINSIP KEHATI-HATIAN DALAM VALUASI HAK KEKAYAAN INTELEKTUAL SEBAGAI JAMINAN FIDUSIAThe Indonesian government passed Government Regulation No. 24 of 2022 concerning implementing regulations for Law No. 24 of 2019 on the Creative economy regulating Intellectual Property Rights (IPR) holders can apply for loans to banking institutions is a potential utilization of the creative economy. Banking institutions before providing capital analyze prospective debtors for loan approval. This research is a solution for banking institutions to apply IPR as a fiduciary guarantee, it needs government support to regulate the IPR valuation mechanism. This research applies normative legal research problem formulation: First, How is the Implementation of IPR as a fiduciary guarantee according to Bank Indonesia Regulation with Government Regulation on Creative Economy? Second, How is the Implementation of Prudential Principles of Fiduciary Financing of IPR as Fiduciary Guarantee? The results of this study found that the government emphasized the utilization of IPR in PP No. 24 of 2022 to provide access to IPR as a guarantee of financing. Bank Indonesia Regulation No.9/6/PBI/2007 as a rule for assessing the quality of assets of banking institutions guided by the prudential principle aims to minimize risk and does not find IPR as a collateral asset. The results of this study provide a view of the potential of the creative economy. PP No. 24 of 2022 states that the economic value of IPR is based on: (a) cost approach, (b) market approach, (c) income approach, (d) valuation based on applicable standards, so it can be used as a general reference to create an independent asset valuation institution in coordination with Banking Institutions.